E-135 Endovascular thrombectomy with or without intravenous thrombolysis in acute basilar artery occlusion ischemic stroke: a meta-analysis. (23rd July 2022) - Schartz, D; Kohli, G; Ellens, N; Akkipeddi, S; Bhalla, T; Mattingly, T; Bender, M
Abstract : Introduction: It is poorly understood if endovascular thrombectomy (EVT) with or without intravenous bridging thrombolysis (IVT) better facilitates clinical outcomes in patients with acute basilar artery occlusion ischemic stroke. Methods: A PRISMA compliant systematic literature review and meta-analysis was completed to investigate the outcomes of EVT with IVT versus direct EVT alone in acute basilar artery stroke. Data was collected from the literature and pooled with the authors' institutional experience. The primary outcome measure was 90-day modified Rankin sale (mRS) of 0–2. Secondary measures were successful post-thrombectomy recanalization defined as mTICI > 2b, 90-day mortality, and rate of symptomatic ICH. A random effects model was used to calculate pooled odds ratios (OR) for each outcome variable. Results: Our institutional experience combined with three multicenter studies resulted in a total of 1, 127 patients included in the meta-analysis. 756 patients underwent EVT alone, while 371 were treated with EVT+IVT. Patients receiving EVT+IVT had a higher odds of achieving a 90-day mRS of < 2 compared to EVT alone (OR: 1.50, 95% CI 1.15 to 1.95, P =0.002, I 2 =0%). EVT+IVT also had a lower odds of 90-day mortality (OR: 0.57, 95% CI 0.37 to 0.89, P=0.01, I 2 =24%). There was no difference in sICH between the two groups (OR: 1.0, 95% CI: 0.56 to 1.79, P=0.99, I 2 =0%). There was also no difference in post-thrombectomy recanalization rates defined as mTICI >2b (OR: 1.11, 95% CI 0.70 to 1.75, P = 0.74, I 2 =37%). Conclusions: On meta-analysis, endovascular thrombectomy with bridging intravenous thrombolysis results in superior 90-day functional outcomes, lower 90-day mortality, and similar sICH compared to direct endovascular thrombectomy alone. These findings likely deserve further validation in a randomized controlled setting. Disclosures: D. Schartz: None. G. Kohli: None. N. Ellens: None. S. Akkipeddi: None. T. Bhalla: None. T. Mattingly: None. M. Bender: None.